Quantitative analysis of chromatin interaction changes upon a 4.3 Mb deletion at mouse 4E2 - Zepeda-Mendoza, Cinthya J.; Mukhopadhyay, Swagatam; Wong, Emily S.; Harder, Nathalie; Splinter, Erik; de Wit, Elzo; Eckersley-Maslin, Melanie A.; Ried, Thomas; Eils, Roland; Rohr, Karl; Mills, Alea; de Laat, Wouter; et al. (BMC genomics, 2015)
Circular chromosome conformation capture (4C) has provided important insights into three dimensional (3D) genome organization and its critical impact on the regulation of gene expression. We developed a new quantitative framework based on polymer physics for the analysis of paired-end sequencing 4C (PE-4Cseq) data. We applied this strategy to the study of chromatin interaction changes upon a 4.3 Mb DNA deletion in mouse region 4E2.
Gesehen am 23.07.2020